Fbxo42 promotes the degradation of Ataxin-2 granules to trigger terminal Xbp1 signaling - Cristiana C. Santos; Nadine Schweizer; Fátima Cairrão; Juanma Ramirez; Nerea Osinalde; Ming Yang; Catarina J. Gaspar; Vanya I. Rasheva; Miguel L. Trigo; Zach Hensel; Colin Adrain; Tiago N. Cordeiro; et al. (Nature Communications)
Abstract The Unfolded Protein Response (UPR) is activated by the accumulation of misfolded proteins in the Endoplasmic Reticulum (ER), a condition known as ER stress. Prolonged ER stress and UPR activation cause cell death, by mechanisms that remain poorly understood. Here, we report that regulation of Ataxin-2 by Fbxo42 is a crucial step during UPR-induced cell death. From a genetic screen in Drosophila, we identify loss of function mutations in Fbxo42 that suppress cell death and retinal degeneration induced by the overexpression of Xbp1spliced, an important mediator of the UPR. We identify the RNA binding protein Ataxin-2 as a substrate of Fbxo42, which, as part of a Skp-A/Cullin-1 complex, promotes the ubiquitylation and degradation of Ataxin-2. Upon ER-stress, the mRNA of Xbp1 is sequestered and stabilized in Ataxin-2 granules, where it remains untranslated. Fbxo42 recruitment to these granules promotes the degradation of Ataxin-2, allowing for the translation of Xbp1 mRNA and triggering cell death during the terminal stages of UPR activation.